742 Linkages between sleep quality and mental health among couples coping with type 1 diabetes across survey and daily diary methods. (3rd May 2021) - Tracy, Eunjin; Berg, Cynthia; Butner, Jonathan; de Grey, Robert Kent; Allen, Nancy; Porter, Margot; Helgeson, Vicki
Abstract: Introduction: Sleep serves an important role in maintaining and promoting metabolic and mental health. The interdependent nature of couple relationships makes examining sleep quality from a dyadic perspective critical. This study examined the effect of sleep quality on mental health among couples coping with type 1 diabetes across survey and daily diary methods and investigated whether relationship satisfaction moderated these relations. Methods: 199 persons with type 1 diabetes (Mage = 46.82) and their spouses (Mage = 46.41) completed one survey questionnaire reporting their own sleep quality (PSQI), depressive symptoms (CESD), and relationship satisfaction (CSI). They also completed 14-day diaries reporting on their own sleep quality and negative affect. The actor-partner interdependence model and multi-level model were used to examine the effect of sleep quality on mental health across the cross-sectional and daily diary surveys. Multi-level modeling examined effects of within-person and between-person effects of sleep quality on next-day daily negative affect (controlling for prior day affect). Results: Cross-sectional survey data revealed an association between poorer global sleep quality and higher depressive symptoms for both partners (actor effects). Spouses' poorer sleep quality was associated with higher depressive symptoms for persons with T1D (partner effects). Daily diary data demonstrated an association between within-person and between-person effects of own poor sleep quality and higher negative affect for both partners. Poorer daily sleep quality for persons with T1D was associated with higher negative affect for spouses (partner effects). When examining the moderating role of relationship satisfaction, spouses' poorer overall sleep quality was associated with greater depressive symptoms and overall negative affect respectively for those with lower relationship satisfaction but not for those with higher relationship satisfaction across both methods. Conclusion: Findings support the conceptualized link between sleep quality and mental health as both an intraindividual and dyadic process among couples coping with T1D across survey and daily diary methods. Additionally, better relationship satisfaction may buffer the effect of overall poor sleep quality on mental health for spouses. Support (if any): This work was supported by NIH NIDDK program project grant (DP3DK103999). Individual support was provided by T32 MH019986 (ELT).